Clinical Features of Drug Eruption in An Indonesian Tertiary Hospital - Rohmawaty, Enny; Devani, Mochamad; Pangastuti, Miranti (Faculty of Medicine, Universitas Padjadjaran, 2025)
Drug eruption is a response to drugs undergoing sensitization, which is mediated by the immune system. Clinical features of drug eruptions, such as maculopapular drug eruption, Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN), and drug reaction with eosinophilia and systemic symptoms (DRESS), are known as common drug reactions. This study aimed to explore the characteristics and clinical features of patients with drug eruptions at the Department of Dermatology and Venereology of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. This retrospective descriptive study used data from the department from patients treated between January 1, 2014 and December 31, 2018. Data were analyzed using Excel and SPSS software. In this study, 200 subjects were included, mainly consisting of female subjects (50.5%) and aged between 19 and 65 (89%). Maculopapular drug eruption (45%) was the most typical clinical presentation, followed by SJS/TEN (37.5%), and DRESS (3%). The analgesics and non-steroidal anti-inflammatory drugs (NSAID) group was the most commonly suspected causative drug (36.91%), with paracetamol (29.18% of total drugs consumed) as the most frequent NSAID causing the eruption. This was followed by the antibiotic-type drugs group (36.48%), with cotrimoxazole (9.87% of total drugs consumed) as the most common one. So, maculopapular drug eruption is the most common clinical presentation of drug eruption, with analgesics and non-steroidal anti-inflammatory drugs (NSAID) class as the most suspected causative drug. Further investigations are needed to get the accurate result.